Pantranscriptome combined with phenotypic quantification reveals germplasm kinship and regulation network of bract color variation in Bougainvillea - Huang, Huaxing; Ji, Hongli; Ju, Song; Lin, Wei; Li, Jing; Lv, Xuanrui; Lin, Lixian; Guo, Lijin; Qiu, Dongliang; Yan, Jianyong; Ma, Xiaokai (Frontiers in Plant Science, 2022)
Bracts are the metamorphic non-flower organ in angiosperms plants. The variation of the color and shape of bracts was found to be neo-functionalized (i.e., similar to petals), garnering research interest as a pollinator attractor. Bougainvillea is known for its specialized, large, and colorful bracts, which contrast with its tiny colorless flower. As a plant whose bracts vary greatly in terms of coloration, the molecular mechanisms for Bougainvillea bract coloration and polychroism is largely unknown. The lack of genomic information for Bougainvillea largely hinders studies into the evolution and genetic basis of bract color variation. In this study, a pan-transcriptome of bracts obtained from 18 B. glabra accessions were employed to investigate the global population level germplasm kinship and the gene regulation network for bract color variation. Our results showed that the bracts of B. glabra accessions have largely differentiated CIE L-a-b values. Besides, germplasm kinship detected using principal component analysis, phylogeny, and admixture analysis showed three optimal subgroups with two of them distinctly clustered, which were not directly correlated with bract color variation at population level. Differentially expressed genes (DEGs) between accessions of high versus low L-a-b values revealed several considerable up-regulated genes related to bract color L-a-b variation. A weighted gene co-expression network was constructed, and eight co-expressed regulation modules were identified that were highly correlated with variation in bract CIE L-a-b color values. Several candidate DEGs as well as co-expressed Hub genes (e.g., GERD, SGR, ABCA3, GST, CYP76AD1, CYP76C, and JAZ) which were tightly associated with bract color variation were eventually determined responsible to L-a-b colorations, which might be the core regulation factors contributing to the B. glabra bract color variation. This study provides valuable insights into the researches of germplasm kinship, population-level pan-transcriptome expression profiles, and the molecular basis of color variation of key innovative bracts in horticultural Bougainvillea.